The Egyptian Elite as Roman Citizens : Looking at Ptolemaic Private Portraiture - Cafici, Giorgia (Harvard Egyptological Studies, 2021)
In The Egyptian Elite as Roman Citizens Giorgia Cafici offers the analysis of private, male portrait sculptures as attested in Egypt between the end of the Ptolemaic and the beginning of the Roman Period. Ptolemaic/Early Roman portraits are examined using a combination of detailed stylistic evaluation, philological analysis of the inscriptions and historical and prosopographical investigation of the individuals portrayed. The emergence of this type of sculpture has been contextualised, both geographically and chronologically, as it belongs to a wider Mediterranean horizon. The analysis has revealed that eminent members of the Egyptian elite decided to be represented in an innovative way, echoing the portraits of eminent Romans of the Late Republic, whose identity was surely known in Egypt.